Examining Racial Segregation in Montessori Schools - David John Fleming; TJ Robertson; Josebell Rivadeneira Cevallos (Journal of Montessori Research)
This study examines racial enrollment patterns in Montessori schools across the United States and evaluates how these schools relate to broader patterns of school segregation. Using a national dataset of public and private Montessori and non-Montessori schools, we analyze Montessori programs’ racial composition, demographic alignment with surrounding districts and neighborhoods, and contribution to within-district segregation. We estimate 37 percent of Montessori students are Black or Hispanic, with notable variation across school sectors. Further, we find Black or Hispanic students are underrepresented in many Montessori schools as compared to school district averages. Our multivariate analyses suggest Montessori schools contribute slightly more to within-district segregation than do non-Montessori schools, primarily due to enrollment patterns in private Montessori schools. Though Montessori education emphasizes inclusivity and cultural responsiveness, variation in enrollment patterns suggests access remains uneven across school sectors. This study examines the relationship between school choice, segregation, and the Montessori model, providing a baseline for evaluating current efforts to improve accessibility and inclusivity in Montessori schools nationwide.